Cyanidin Chloride Induces Apoptosis by Inhibiting NF-κB Signaling through Activation of Nrf2 in Colorectal Cancer Cells - Da-Young Lee; Sun-Mi Yun; Moon-Young Song; Kiwon Jung; Eun-Hee Kim (MDPI AG, 2020)
Colorectal cancer (CRC) is the third most common cancer worldwide and a leading cause of cancer-related deaths in developed countries. Anthocyanins are a class of flavonoids, widely distributed in food, exhibiting important biological effects. Cyanidin chloride (CyCl) is the common type of anthocyanin with antioxidative and anti-inflammatory potential. The present study aimed to investigate the molecular mechanisms underlying the chemotherapeutic effects of CyCl in colorectal cancer cells. We found that CyCl treatment induced apoptosis as well as a significant inhibition of cellular proliferation and colony formation in three colon cancer HCT116, HT29, and SW620 cells. In addition, CyCl suppressed nuclear factor-kappa B (NF-κB) signaling and induced the activation of the nuclear factor erythroid 2-related factor 2 (Nrf2) pathway in tumor necrosis factor-alpha (TNF-α)-stimulated colon cancer cells. Nrf2 and NF-κB are two key transcription factors regulating antioxidative responses and cellular proliferation, respectively. In this study, knockdown of Nrf2 by small interfering RNA (siRNA) transfection inhibited the effect of CyCl on NF-κB signaling and apoptosis, suggesting that there is functional crosstalk between Nrf2 and NF-κB. Our findings demonstrate the important role of Nrf2 in inducing apoptosis through the involvement of NF-κB signaling in colorectal cancer cells, suggesting that CyCl may be used as a potential therapeutic agent for CRC.